Carrier‐Free ATP‐Activated Nanoparticles for Combined Photodynamic Therapy and Chemotherapy under Near‐Infrared Light. Issue 11 (1st January 2023) - Su, Zehou; Xi, Dongmei; Chen, Yingchao; Wang, Ran; Zeng, Xiaolong; Xiong, Tao; Xia, Xiang; Rong, Xiang; Liu, Ting; Liu, Wenkai; Du, Jianjun; Fan, Jiangli; et al.
Abstract: The combination of photodynamic therapy (PDT) and chemotherapy (chemo‐photodynamic therapy) for enhancing cancer therapeutic efficiency has attracted tremendous attention in the recent years. However, limitations, such as low local concentration, non‐suitable treatment light source, and uncontrollable release of therapeutic agents, result in reduced combined treatment efficacy. This study considered adenosine triphosphate (ATP), which is highly upregulated in tumor cells, as a biomarker and developed ingenious ATP‐activated nanoparticles (CDNPs) that are directly self‐assembled from near‐infrared photosensitizer (Cy‐I) and amphiphilic Cd(II) complex (DPA‐Cd). After selective entry into tumor cells, the positively charged CDNPs would escape from lysosomes and be disintegrated by the high ATP concentration in the cytoplasm. The released Cy‐I is capable of producing single oxygen ( 1 O2 ) for PDT with 808 nm irradiation and DPA‐Cd can concurrently function for chemotherapy. Irradiation with 808 nm light can lead to tumor ablation in tumor‐bearing mice after intravenous injection of CDNPs. This carrier‐free nanoparticle offers a new platform for chemo‐photodynamic therapy. Abstract : ATP‐activatable nanoparticles (CDNPs), which is composed by near‐infrared photosensitizer (Cy‐I) and amphiphilic Cd(II) complex (DPA‐Cd) via self‐assembly, can enter into tumor cells and make a quick escape from lysosomes. Through interaction with cytoplasmic adenosine triphosphate (ATP), Cy‐I and DPA‐Cd will be released from CDNPs and function for chemo‐photodynamic therapy under 808 nm laser.